Evaluation of correction of kyphotic deformity in dorso-lumbar spinal injuries by posterior stabilization with pedicular screw rod fixation - Srinivasan, N.; Prabhakar, Y. V. S. (International Journal of Research in Orthopaedics, 2018)
Background: Acute injury to dorso-lumbar spine is the second most frequent site after cervical spine in adults. The injury, although not associated with high mortality, causes severe morbidity. The management of the traumatic dorso-lumbar spine injuries has improved considerably in the last few years. The objective of the study was to evaluate correction of kyphotic deformity in dorso-lumbar spinal injuries by posterior stabilization with pedicular screw rod fixation. Methods: The study includes 52 patients with dorso-lumbar spinal injuries with or without neurological deficit treated between 2006 and 2014. Pre and postoperative kyphosis was measured by Cobb’s method on plain radiographs. Pre and postoperative neurological status was evaluated based on Frankel’s classification. All un-stable dorso-lumbar spine injuries where two or more columns are involved on X-ray and CT scan were included in the present study. Results: Majority of the patients were in the age group of 20-30 years (38.5%) followed by 31-40 years (30.8%). Males were more than females. The most common mode of injury was road traffic injury in 71.2% of the cases. The most common level of injury was at L1 in 28.8% of the cases followed by at level D12 in 25% of the cases. In all the groups the mean kyphosis angle is reduced significantly. Overall the improvement rate was 94.2% and failure rate was only 5.8%. Conclusions: In conclusion the posterior reduction and internal fixation is a useful procedure in the treatment of the acute injuries of the dorsolumbar spine.